Front Cover: Fluorophore Release from a Polymethinic Photoremovable Protecting Group Through a Nonlinear Optical Process (ChemPhotoChem 9/2017). Issue 9 (7th September 2017) - Rodríguez‐Romero, Jesús; Guarin, Cesar A.; Arroyo‐Pieck, Andres; Gutiérrez‐Arzaluz, Luis; López‐Arteaga, Rafael; Cortés‐Guzmán, Fernando; Navarro, Pedro; Peon, Jorge
Abstract : The Front Cover picture represents a two‐photon‐induced release event in a 3D spatially localized region. More information can be found in the Article by J. Peon and co‐workers onpage 397 in Issue 9, 2017 (DOI:10.1002/cptc.201700076 ).